COMMUNITY EMPOWERMENT IN THE FIELDS OF EDUCATION ENTREPRENEURSHIP AND THE ENVIRONMENT IN THE VILLAGE - Amri, Miftachul; Asfahani, Asfahani; Kadeni, Kadeni; Arif, Muh.; Jamin, Fitriah Suryani (Community Development Journal : Jurnal Pengabdian Masyarakat, 2024)
Community Empowerment in the Fields of Education, Entrepreneurship, and the Environment in Villages is a comprehensive initiative encouraging holistic development and empowerment of rural communities. This service activity aims to empower the community through an integrated approach that addresses education, entrepreneurship, and the environment. This service method uses Participatory Action Research (PAR), which involves participatory needs assessments, tailored educational programs, entrepreneurial empowerment initiatives, and environmental awareness campaigns. Collaborative partnerships with community stakeholders, educators, entrepreneurs, and environmental advocates are integral to the success of this initiative. The results of this service show increased learning outcomes, entrepreneurial skills, and awareness of the environment in the village. Through local education, small-scale business support, and sustainable practices, community members have gained agency, economic security, and a sense of environmental responsibility. The success of this initiative underscores the interconnectedness of these pillars in promoting comprehensive community empowerment. So, the Community Empowerment initiative is a model for inclusive and sustainable development strategies in rural areas.